A Real-Time Measurement Model of Attention-Allocation Level and Its Application in Simulated SPO Task - Lei Wang; Zhiyang Zhang; Wei Tan; Zhongchang Yang (International Journal of Aerospace Engineering)
Most human-caused flight accidents can be attributed to a pilot’s attention deficit and monitoring errors. Accordingly, pilots’ attention allocation is strongly related to their task performance. This study is aimed at analyzing pilots’ fixation characteristics and attention-allocation levels. First, we proposed a model for measuring attention-allocation level based on the salience, effort, expectancy, and value (SEEV) model. Second, a low-fidelity single-pilot operation (SPO) cockpit environment was constructed, and 20 pilots were recruited for an experiment to compare their fixation characteristics between SPO and double-pilot operation (DPO) scenarios. The results showed slight differences in the attention levels allocated by SPO and DPO pilots under a scenario of one-engine failure. It concluded that Human-centered flight deck design can enhance a pilot’s attention allocation level. These findings can be used to optimize future flight deck designing and flight training for improving pilot’s task performance.